“We are also Africans” - Ntshona, Onele Lebuhang (Rhodes University, 2026)
English monolingualism among black African youth is a growing phenomenon in post-apartheid South Africa, particularly among those raised in urban areas. This trend carries significant implications, as these individuals must navigate their identities as black Africans within a context where language is deeply intertwined with ethnic identity. This dissertation explores the development of English monolingualism among black African youth, focusing on how their environments and social contexts have shaped the predominance of English. It further examines the implications of this monolingualism for individuals from cultures and ethnic groups with distinct linguistic traditions. Additionally, the study investigates the social construction of ‘blackness’, focusing on how it is defined, understood, reproduced, and reinforced within society. This study examines the interplay between language, identity, and social interaction among monolingual English-speaking black African youth (aged 20 to 30) raised in urban areas in South Africa interacting within African social environments in South Africa. Addressing a gap in existing literature, it centres on individuals who reside in their native environments but lack proficiency in their ancestral language. Using symbolic interactionist and social constructionist theoretical frameworks, this qualitative study highlights how these youth navigate social interactions and identity formation, emphasising the role of language in shaping their experiences. Through purposive and snowball sampling techniques, seven in-depth interviews were conducted to capture the nuanced experiences of participants. Findings provide insights into how these youth perceive and define "blackness," their personal identities, and the circumstances shaping their experiences. Additionally, the study highlights the complexities of language use in social interactions and cultural connectedness, revealing the tension between personal identities and societal expectations. This study thus contributes to a deeper understanding of the role of language in shaping identity and social interaction, offering insights into the lived experiences of black African young adults in South Africa. By amplifying their voices, the study aims to provide valuable insights into the lived realities of monolingual English-speaking black African individuals living in South Africa.
exploring the experiences of monolingual English-speaking black African youth interacting in black African Communities in South Africa
Keywords: Uncatalogued